Theory of the gimmick : aesthetic judgement and capitalist form - Ngai, Sianne (The Belknap Press of Harvard University Press, 2020)
"The gimmick lies latent in every made thing in capitalism, from the banana slicer to the cryptocurrency derivative to the readymade artwork that interprets itself. It includes both the painstakingly devised and the gratuitously disposable. It is what we call things when uncertain if they are over- or underperforming, if they are historically backward or just as problematically advanced, if they are wonders or tricks. With its promises about the saving of time; the reduction of labor; and the expansion of value, the gimmick gives us tantalizing glimpses of a world in which social life will no longer be organized by labor, but also of one regenerating the conditions that keep labor's social necessity in place. As Ngai takes us from the hoaxes of Edgar Allen Poe to artist Stan Douglas's interest in outmoded special effects, we begin to see how the aesthetic manipulation of the gimmick points to a much deeper exploitation. Against academic claims about Marx's value-labor theory's obsolescence, the gimmick reveals it as vibrantly alive in the realm of aesthetics"